tg²α-sin²α=tg²α*sin²α
sin²α/cos²α-sin²α=sin²α/cos²α*sin²α
(sin²α-sin²αcos²α)/cos²α=sin⁴α/cos²α
sin²α*(1-cos²α)/cos²α=sinα/cos²α
sin⁴α/cos²α=sin⁴α/cos²α ч.т.д.
sin³α(1+ctqα) +cos³α(1+tqα) =sinα+cosα.
sin³α(1+ctqα) +cos³α(1+tqα) =sin³α+cos³α +sin²αcosα +sinαcos²α =
(sinα+cosα)(sin²α -sinαcosα +cos²α ) +sinαcosα(sinα +cosα) =
(sinα+cosα)(sin²α -sinαcosα +cos²α +sinαcosα) =(sinα+cosα)(sin²α+cos²α)=
(sinα+cosα)*1 =sinα+cosα.
Фух...надеюсь правильно:)
tg²α-sin²α=tg²α*sin²α
sin²α/cos²α-sin²α=sin²α/cos²α*sin²α
(sin²α-sin²αcos²α)/cos²α=sin⁴α/cos²α
sin²α*(1-cos²α)/cos²α=sinα/cos²α
sin⁴α/cos²α=sin⁴α/cos²α ч.т.д.
sin³α(1+ctqα) +cos³α(1+tqα) =sinα+cosα.
sin³α(1+ctqα) +cos³α(1+tqα) =sin³α+cos³α +sin²αcosα +sinαcos²α =
(sinα+cosα)(sin²α -sinαcosα +cos²α ) +sinαcosα(sinα +cosα) =
(sinα+cosα)(sin²α -sinαcosα +cos²α +sinαcosα) =(sinα+cosα)(sin²α+cos²α)=
(sinα+cosα)*1 =sinα+cosα.
Фух...надеюсь правильно:)